Development of Ethnoscience-Based Digital Student Worksheets to Improve Scientific Literacy and Critical Thinking Skills of Elementary School Students - Purnama Indra; Antonius Totok Priyadi; Ricka Tesi Muskania (Journal of General Education and Humanities, 2026)
Science and Social Studies (IPAS) learning in elementary schools still faces challenges in strengthening students’ scientific literacy and critical thinking skills because the learning process tends to be textual, less contextual, and has not optimally integrated local culture and digital technology. This study aims to develop an ethnoscience-based digital student worksheet (LKPD) that is valid, practical, and effective in improving elementary school students’ scientific literacy and critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved 28 elementary school students. Data were collected through observation, interviews, questionnaires, tests, and documentation, and then analyzed using descriptive statistics and the N-gain test. The results showed that the ethnoscience-based digital LKPD obtained an average validation score of 91.1%, categorized as highly valid. The implementation of the product demonstrated an improvement in scientific literacy with an N-gain score of 0.71 and critical thinking skills with an N-gain score of 0.69. The integration of local culture, interactive multimedia, and project-based learning proved to enhance students’ engagement, scientific reasoning, and problem-solving abilities. These findings confirm that the ethnoscience-based digital LKPD is effective in supporting contextual IPAS learning and 21st-century learning in elementary schools.